IMPLICATION OF REMIDING RIDWAN REMIN IN STAND UP COMEDY EVENTS - Masroi, Nazilul _ (Universitas Andalas, 2020)
AbstractImplications are a theory maybe the meaning is implied rather than explicit. Studies on these implicatures can be found on every day life as seen in the stand up comedy discourse by Ridwan Remin. Thi study aims to explain the types of implicature contained in thestand up comedy by Ridwan Remin, as well as to explain the nature of the implicature contained in the discourse. The approach used on research is a theoretical and methodological approach. The teoretical approach in this study uses a pragmatis approach, meaning that the date are analyzed by describing the pragmatic meaning in linguistic units. The methodological approach in this research is a qualitative descriptive approach. Data in research is stand up comedy discourse by Ridwan Remin. Data collection was carried out by listening techniques, documentation techniques, an note taking techniques. The result of this study indicate that three are two types of implicatures, namely: 1) conversational implicatures with the intention of rejecting, insinuating, guessing, asking, scolding; and 2) conventional implicatures with the intention of complaining, insinuating, telling. The benefit of this researchis to find out the types of Ridwan Remin implicatures in the Stand up comedy event.